Alcyonacean Metabolites VIII-Antibacterial metabolites from Labophytum crassum of the Indian Ocean - Vanisree, Mulabagal; V Subbaraju, Gottumukkala (Asian Journal of Chemistry, 2010)
Bioassay guided fractionation of the ethyl acetate soluble fraction of the soft coral Lobophytum crassum yielded a cembranoid diterpene [(7E, 11E,1R,2S,3R,4R,14S)-14-acetoxy-3,4-epoxycembra-7,11,15-triene-17,2-olide, 1] as the potent anti-bacterial metabolite exhibiting activity against Pseudomonas aeroginosa, Staphylococcus epidermis, Staphylococcus aureus and Bacillus subtilis. A new ceramide (2) with moderate antibacterial activity besides two known polyhydroxysterols and batyl alcohol were also isolated.